"The Cult of Greta Thunberg": De-legitimating Climate Activism with "Religion" - Kyyrö Jere; Äystö Tuomas; Hjelm Titus (SAGE PUBLICATIONS INC, 2025)
Contemporary climate activism has often been called a "religion" or a "cult." We investigate what is done with climate religion discourse (CRD), by whom, and to what ends. Our case study concerns Finland, one country out of many where forms of climate activism are regularly dismissed by equating them with "irrational" religion. We find that political parties and newspaper columnists use terms and phrases such as "millenarianism," "prophet," "Messiah," "cult," "apocalypse," "Virgin Mary of climate religion," and "children's crusade." We argue that these are examples of strategic othering in the Finnish context. We observe that this religionizing stems from the activism's incompatibility with prevalent economic rationality, and that gender is a significant theme in CRD use. An unintended consequence of CRD is that it constructs those forms of religion, which do not disturb modernity and the capitalist order as more legitimate than others.